Examining Post-School Outcomes of Indonesian Secondary Students with Disabilities: A Policy Document Analysis - Ariwijaya, Toni (Indonesian Journal of Disability Studies, 2021)
There are no national laws in Indonesia which requires educational authorities to provide Invidualised Transition Plans (ITPs) towards high school students with disabilities. It leads issues as to low education attainments the students from this population have as well as small numbers of the students entering universities and job markets. In lieu of legislations, it is argued that Indonesia has signed international agreement and policies which are actually meant to provide ITPs to secondary students with disabilities to improve their post school outcomes education, employment and independent living for this vulnerable group. Hence, document analysis methods were employed in this research to analyse the international, national and local policies that the country has been signed through analyzing the statements aligned with evidence-based transition skills and predictors. The method employed by O'Neill et al. (2016) was replicated to condense the list of practices in the NTACT website into broader categories to address youths academic, employment, and independent living needs. As for the international policy, 19 transition-aligned statements were found, accounting for community involvement, interagency collaboration and inclusion in general education. Meanwhile for the national policy documents, only 15 statements were aligned. Implication for policymakers and educational jurisdictions are also discussed.